Windows Server 2003: Best Practices for Enterprise Deployments - Ruest, Danielle (McGraw-Hill, 2011)
Discover the fastest way to migrate to Windows Server 2003 and begin to profit from its enterprise-ready features. Learn how to use the parallel network - a migration approach that provides constant rollback and limited impact on your existing network. Build your new network from the ground up. Begin by designing your Enterprise Network Architecture and then move on to feature by feature implementations. Learn to make the most of Active Directory as an object management environment to remotely configure PCs, Servers, Users and Groups.